Coping Strategy and Psychological Well-Being of Final Year University Student - Yuni Syaudah (Psychological Research and Intervention, 2019)
This study aims to determine the coping strategies and level of psychological well-being of final year university student, as well as predicting psychological well-being of final year university student based on their coping strategies. This study employs quantitative approach with ex post facto research type. This study involves 135 university students from Faculty of Education Universitas Negeri Yogyakarta by means of accidental sampling technique. Data was collected through the coping scale (problem focused coping scale and emotional focused coping scale) and psychological well-being scale. The result of this study shows that coping strategy was able to predict psychological well-being (p = 0,000; p α 0,05). Problem focused coping and emotional focused coping can predict psychological well-being by 12%. The regression equation line obtained is Y = 132,05+0,819x1-0,501x2